1999
DOI: 10.1136/jech.53.3.149
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of varicose veins and chronic venous insufficiency in men and women in the general population: Edinburgh Vein Study

Abstract: Study objective-To determine the prevalence of varicose veins and chronic venous insuYciency (CVI) in the general population. Design-Cross sectional survey. Setting-City of Edinburgh. Participants-Men and women aged 18-64 years selected randomly from age-sex registers of 12 general practices. Main results-In 1566 subjects examined, the age adjusted prevalence of trunk varices was 40% in men and 32% in women (p<0.01). This sex diVerence was mostly a result of higher prevalence of mild trunk varices in men. More… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
551
6
55

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 767 publications
(625 citation statements)
references
References 9 publications
13
551
6
55
Order By: Relevance
“…O ponto em que parece haver discordância é que, no nosso trabalho, mesmo não havendo sinais externos que possam levantar suspeita de hipertensão venosa, a FVR (que, para alguns autores 16,21 , se relaciona com a pressão venosa ambulatorial) ocorreu em 86,7% dos pacientes que apresentaram níveis acima de Figura 2 -Análise de correspondência para fração de ejeção da perna direita (efdircod), fração de ejeção da perna esquerda (efesqcod), fração do volume residual da perna direita (rvfdircod), fração do volume residual da perna esquerda (rvfesqcod) nos grupos com refluxo e sem refluxo 60%, sendo este dado estatisticamente relevante. Há, porém, concordância com a literatura quanto ao fato de que o VE não apresenta diferenças estatisticamente significativas para ambos os sexos 23 . Embora a complacência venosa esteja alterada, em função do refluxo encontrado, não há influência para a hemodinâmica venosa 24 .…”
Section: Discussionunclassified
“…O ponto em que parece haver discordância é que, no nosso trabalho, mesmo não havendo sinais externos que possam levantar suspeita de hipertensão venosa, a FVR (que, para alguns autores 16,21 , se relaciona com a pressão venosa ambulatorial) ocorreu em 86,7% dos pacientes que apresentaram níveis acima de Figura 2 -Análise de correspondência para fração de ejeção da perna direita (efdircod), fração de ejeção da perna esquerda (efesqcod), fração do volume residual da perna direita (rvfdircod), fração do volume residual da perna esquerda (rvfesqcod) nos grupos com refluxo e sem refluxo 60%, sendo este dado estatisticamente relevante. Há, porém, concordância com a literatura quanto ao fato de que o VE não apresenta diferenças estatisticamente significativas para ambos os sexos 23 . Embora a complacência venosa esteja alterada, em função do refluxo encontrado, não há influência para a hemodinâmica venosa 24 .…”
Section: Discussionunclassified
“…There are studies that claim that there is only a relationship between obesity and CVI, 3,6,24 or an association between varicose veins and BMI, among women, 1,5,14,25 and others that found no evidence of any relationship. 14,26 It does not appear likely that obesity could be a risk factor for one sex but not for the other, and it can be considered as an aggravating factor in venous disease.…”
Section: Discussionmentioning
confidence: 99%
“…This result contrasts with data reported by Andreozzi et al, 9 since they found a relationship between hypotonic phlebopathy and obesity, but it is in line with other results in the literature indicating that the association between BMI and varicose veins is stronger among women. 1,5,14,25 Another factor investigated was distribution by age group of the hypotonic phlebopathy patients. This analysis showed that the highest prevalence (64%) is among younger people aged < 30 years (2:1) and that prevalence reduces as age increases, as symptoms become more likely to be related to anatomic venous injuries.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations